2008
DOI: 10.1101/gad.1615208
|View full text |Cite
|
Sign up to set email alerts
|

Functionally distinct regulatory RNAs generated by bidirectional transcription and processing of microRNA loci

Abstract: Many microRNA (miRNA) loci exhibit compelling hairpin structures on both sense and antisense strands; however, the possibility that a miRNA gene might produce functional species from its antisense strand has not been examined. We report here that antisense transcription of the Hox miRNA locus mir-iab-4 generates the novel pre-miRNA hairpin mir-iab-8, which is then processed into endogenous mature miRNAs. Sense and antisense iab-4/iab-8 miRNAs are functionally distinguished by their distinct domains of expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
214
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 183 publications
(226 citation statements)
references
References 32 publications
8
214
1
2
Order By: Relevance
“…These findings suggest that with the continuous availability of genome sequences, we could identify many more miRNAs that regulate important genes in B. rapa. The transcription of miRNAs from sense and antisense strands is recently reported in insects, human, and plants (Bender, 2008;Stark et al, 2008;Tyler et al, 2008;Zhang et al, 2008). In the present study, we found only 1 DNA sequence from which both sense and antisense mature miRNAs were produced compared to 5 miRNAs belonging to 3 families identified in soybean ; the sense and antisense miRNAs differ by 1-3 nt in that study.…”
Section: Discussionsupporting
confidence: 51%
“…These findings suggest that with the continuous availability of genome sequences, we could identify many more miRNAs that regulate important genes in B. rapa. The transcription of miRNAs from sense and antisense strands is recently reported in insects, human, and plants (Bender, 2008;Stark et al, 2008;Tyler et al, 2008;Zhang et al, 2008). In the present study, we found only 1 DNA sequence from which both sense and antisense mature miRNAs were produced compared to 5 miRNAs belonging to 3 families identified in soybean ; the sense and antisense miRNAs differ by 1-3 nt in that study.…”
Section: Discussionsupporting
confidence: 51%
“…It has been described previously that miRNA loci can be transcribed from both strands to form mature miRNAs (Ruby et al 2007a;Tyler et al 2008). We found one locus that produced putative miRNAs from both directions and one locus that only produced an antisense miRNA to a known miRNA.…”
Section: Discussionmentioning
confidence: 66%
“…As more highthroughput data is acquired, these as well as other antisense loci are likely to be annotated as miRNA genes. However, <0.00002 of our miRNA reads corresponded to miRNAs from antisense loci (excluding the reads mapping ambiguously to mir-486/mir-3107), raising the possibility that none of the murine antisense miRNAs have a function comparable with that of miR-iab-as in flies (Bender 2008;Stark et al 2008;Tyler et al 2008).…”
Section: General Features Of Mammalian Mirnasmentioning
confidence: 97%